2017
DOI: 10.1371/journal.pone.0183182
|View full text |Cite
|
Sign up to set email alerts
|

Early life predictors of adolescent suicidal thoughts and adverse outcomes in two population-based cohort studies

Abstract: BackgroundUnderstanding suicidality has proven challenging given the complex aetiology in early childhood. Being able to accurately predict groups at increased risk of developing suicidal thoughts may aid in the development of targeted prevention programs that mitigate increased vulnerability. Further, the predictors of suicidal thoughts may be shared with other outcomes in adolescence. Previous research has linked many factors to suicidality, so the objective of this study was to consider how these factors ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
0
21
0
3
Order By: Relevance
“…Early-life adversity (ELA) is associated with increased risk for suicide (Johnson et al, 2002; Labonte and Turecki, 2012; Turecki et al, 2012; Dykxhoorn et al, 2017; Youssef et al, 2018) and adult depression (Miniati et al, 2010; Harkness et al, 2012; Heim and Binder, 2012; Nanni et al, 2012). We found lower neuron density in depressed suicide decedents and hypothesized lower neuron density contributes to higher levels of postsynaptic 5-HT 1A and 5-HT 2A receptors (Underwood and Arango, 2011; Underwood et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Early-life adversity (ELA) is associated with increased risk for suicide (Johnson et al, 2002; Labonte and Turecki, 2012; Turecki et al, 2012; Dykxhoorn et al, 2017; Youssef et al, 2018) and adult depression (Miniati et al, 2010; Harkness et al, 2012; Heim and Binder, 2012; Nanni et al, 2012). We found lower neuron density in depressed suicide decedents and hypothesized lower neuron density contributes to higher levels of postsynaptic 5-HT 1A and 5-HT 2A receptors (Underwood and Arango, 2011; Underwood et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…During adolescence, alcohol and tobacco use, insufficient and unbalanced nutrition, use of addictive substances, unsafe sexual activity, and violence are risky health behaviors [ 21 ] and they tend to increase during this period [ 22 ]. The effort of adolescents to be accepted among friends, the desire to be treated as an adult, and effort to create a new identity result in risk taking and risky health behaviors [ 21 , 23 – 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is a leading cause of death for youth (Cash & Bridge, 2009). Numerous potential risk or protective factors have been linked to adolescent suicidal thought (Evans et al, 2004); a recent review found 75 factors that increase or decrease risk for suicidality in adolescence (Dykxhoorn et al, 2017); however, a high proportion of these factors are non‐modifiable or weakly amenable to intervention (Evans et al, 2004).…”
Section: Introductionmentioning
confidence: 99%